2015
DOI: 10.1002/cbin.10458
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LncRNAs/mRNAs related to endometrium function regulated by Homeobox A10 in Ishikawa cells

Abstract: As a well-known transcription factor, Homeobox A10 (HOXA10) regulates a large number of downstream target genes, leading to the proper function development of endometrium for embryo implantation. The change of HOXA10 gene expression level can alter the expressions of many other genes, including coding and noncoding transcripts. In our study, mRNA and LncRNA expression profiles screening was performed by microarray when the HOXA10 gene expression level increased in Ishikawa cells. A total of 907 mRNAs and 1,026… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…LINC00641 has been reported to be one of the 20 differentially expressed LncRNAs and mRNAs dysregulated through HOXA10 overexpression; for example, in one study, it showed downregulation with fold changes ≥ 2 and P < 0.05 ( 47 ). On the other hand, much evidence shows that several homeobox genes such as HOXA10 are dysregulated in cancers, significantly contributing to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00641 has been reported to be one of the 20 differentially expressed LncRNAs and mRNAs dysregulated through HOXA10 overexpression; for example, in one study, it showed downregulation with fold changes ≥ 2 and P < 0.05 ( 47 ). On the other hand, much evidence shows that several homeobox genes such as HOXA10 are dysregulated in cancers, significantly contributing to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor HOXA10, which is important in fertility through affecting endometrial decidualization and embryo implantation, is also capable of significantly altering mRNA and lncRNA expression involved in the processes of blood vessel development, cell cycle and oocyte meiosis. Thus, lncRNAs are necessary in the normal physiology of women, in preparation for pregnancy (Lin et al, ). Expression profiles of lncRNAs were altered in patients with endometriosis, compared to healthy individuals.…”
Section: Lncrnas In Wnt‐mediated Pathogenesis In Female Reproductive mentioning
confidence: 99%